Maintaining Vascular Access Response in a Severely COVID-19 Hit Country - Castro, João Diogo (2023)
Introduction: The COVID-19 pandemic has caused an unprecedented disruption in healthcare systems worldwide, and Portugal was no exception. We analyze the impact of the COVID-19 pandemic in activity of our Vascular Access Center (Grupo Estudos Vasculares - GEV). Material and methods: This is a retrospective study, during March 2019 and February 2021. An analysis of surgical and appointments records in 2,495 patients from 25 hemodialysis centers followed by GEV was performed. Patients were divided into two periods: non-pandemic (NPP) (March 2019 to February 2020) and pandemic periods (PP) (March 2020 to February 2021). The number of surgeries and appointments were analyzed per month and per week. The number of thrombosis were analyzed in both periods. Normality was tested by the Shapiro-Wilk test and by the Lilliefors (Kolmogorov-Smirnov) test. Comparisons were made by the t-test (paired samples) when normality was not rejected and by the Wilcoxon test otherwise. All the variables (normal or otherwise) were described by the usual descriptive measures such as the mean, median and quartiles. No categorical data were collected. To avoid COVID-19 infection a set of measures were created: Sars-cov-2 PCR test for every patient, individual protection equipment for staff, rotating teams and schedules, and only one patient allowed in the circuit to the intervention room. A descriptive statistical analysis was performed with SPSS version28. The statistical significance was confirmed for p-value < 0.05. Results: A total of 1756 surgeries and 800 appointments were made in both PP and NPP. Comparing the periods, we performed 914 (52%) interventions in the NPP and 842 (48%) in PP, 423 (53%) consultations in NPP and 377 (47%) at PP. Comparing the NPP and PP by months we observed more appointments in the NPP (p=0.004). However, the difference in the number of surgeries did not reach statistical significance (p=0.533). There were more thrombosis during the summer and fall in the NPP and PP. A total of 138 in NPP and 131 in PP thrombosis were observed in the 2 years period. There was no record of COVID-19 infections between all GEV staff (n=25). Conclusion: Due to timed and tight set of measures taken in the pandemic lockdown by GEV, a similar clinical and surgical activity regarding hemodialysis patients was obtained in both periods (PP and NPP). The hypothesis that the PP could diminish vascular access assessment/intervention or more thrombosis could occur was not verified at our institution. The set of measures established to deal with the COVID-19 pandemic was also effective to prevent infection in staff members